Methane Disintegration by Water Vapor in a Hot Chamber heated by Using a Microwave Steam Torch - Choi, Chang H.; Lee, Joo Y.; Kim, Dong J.; Woo, Sang G.; Uhm, Han S. (Journal of the Korean Physical Society, 2019)
An analysis of the behaviors of water and methane in a hot chamber indicates that methane and water molecules mutually help to disintegrate each other. Oxygen atoms from water disintegrate methane, and methane also self-dissociates. A substantial dissociation of methane by these processes occurs at chamber temperatures higher than T = 1500 K. Methyl (CH3) from these dissociations is very instrumental for the disintegration of water molecules. Meanwhile, the majority of methyl molecules undergo disintegration by oxygen atom, producing an abundance of formaldehyde (CH2O), which self-dissociates immediately to carbon monoxide and hydrogen molecules. Hydroxyl (OH) may convert carbon monoxide to carbon dioxide at a very high temperature of T = 1900 K. An experimental observation shows that methane dissociates in a hot steam chamber heated by a microwave torch. Methane disintegrates completely at temperature higher than 1200 °C (= 1480 K) without any catalyst, as expected from the analytical study.
Keywords: 51.10.+y; 52.25.−b; 88.05.Bc; 88.05.Gh; 88.05.−b; Gasification; Hydrogen Production; Methane; Steam Plasma